High-throughput gene targeting and phenotyping in zebrafish using CRISPR/Cas9 - Varshney, Gaurav K.; Pei, Wuhong; LaFave, Matthew C.; Idol, Jennifer; Xu, Lisha; Gallardo, Viviana; Carrington, Blake; Bishop, Kevin; Jones, MaryPat; Li, Mingyu; Harper, Ursula; Huang, Sunny C.; et al. (Genome research, 2015)
The use of CRISPR/Cas9 as a genome-editing tool in various model organisms has radically changed targeted mutagenesis. Here, we present a high-throughput targeted mutagenesis pipeline using CRISPR/Cas9 technology in zebrafish that will make possible both saturation mutagenesis of the genome and large-scale phenotyping efforts. We describe a cloning-free single-guide RNA (sgRNA) synthesis, coupled with streamlined mutant identification methods utilizing fluorescent PCR and multiplexed, high-throughput sequencing. We report germline transmission data from 162 loci targeting 83 genes in the zebrafish genome, in which we obtained a 99% success rate for generating mutations and an average germline transmission rate of 28%. We verified 678 unique alleles from 58 genes by high-throughput sequencing. We demonstrate that our method can be used for efficient multiplexed gene targeting. We also demonstrate that phenotyping can be done in the F 1 generation by inbreeding two injected founder fish, significantly reducing animal husbandry and time. This study compares germline transmission data from CRISPR/Cas9 with those of TALENs and ZFNs and shows that efficiency of CRISPR/Cas9 is sixfold more efficient than other techniques. We show that the majority of published “rules” for efficient sgRNA design do not effectively predict germline transmission rates in zebrafish, with the exception of a GG or GA dinucleotide genomic match at the 5′ end of the sgRNA. Finally, we show that predicted off-target mutagenesis is of low concern for in vivo genetic studies.